The Role of PKC-θ in CD4+ T Cells and HIV Infection: To the Nucleus and Back Again - Phetsouphanh, Chansavath; Kelleher, Anthony D. (Frontiers in Immunology, 2015)
PKC-θ is the only member of the PKC family that has the ability to translocate to the immunological synapse between T cells and APCs upon TCR and MHC-II recognition. PKC-θ interacts functionally and physically with other downstream effector molecules to mediate T cell activation, differentiation and migration. It plays a critical role in the generation of Th2 and Th17 responses and is less important in Th1 and CTL responses. PKC-θ has been recently shown to play a role in the nucleus, where it mediates inducible gene expression in the development of memory CD4+ T cells. This novel PKC can up-regulate HIV-1 transcription and PKC- θ activators such as Prostratin have been used in early HIV-1 reservoir eradication studies. The exact manner of the activation of virus by these compounds and the role of PKC-θ, particularly its nuclear form and its association with NF-κB in both the cytoplasmic and nuclear compartments needs further precise elucidation especially given the very important role of NF-κB in regulating transcription from the integrated retrovirus. Continued studies of this novel PKC isoform will give further insight into the complexity of T cell signaling kinases.